Gen Z Human Resources Analysis in Innovation Management Drivers - Miranti Pradipta Utami; Sugeng Karyadi; Ratnawita; Dharnita Chandra; Lasrida Sigalingging (Indonesian Journal Economic Review (IJER), 2026)
Generation (Gen) Z is emerging as a transformative force redefining the innovation management landscape through their unique characteristics, born and raised amidst the digital technology boom. As digital natives, they don't simply use technology but internalize it as an extension of their way of thinking, enabling a more agile and adaptive innovation process. The purpose of this study is to analyze Gen Z human resources analysis in innovation management drivers. The research method used in this study is qualitative research. The data used in the study are secondary data from copies of books and journals. The research results show that Gen Z is bringing a significant paradigm shift in innovation management. They are not merely technology users, but rather act as catalysts, transforming how organizations create, adopt, and disseminate new ideas. This paradigm shift in innovation management is toward values-based innovation, the democratization of ideas, and digital fluency.